Navigating the Economic Landscape: VAR Analysis and Strengthening the Bank Lending Channel's Impact on Monetary Policy - Prawidya Hariani Rusli Saat; Sylvia Vianty Ranita; Esther Sri Astuti Soeryaningrum Agustin; Wilda Farida Husnul Sinaga (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2024)
In the last 12 years, the percentage of economic growth in Indonesia can be said to have had a downward trend, but the value did not drop drastically but slowly from 6.81% in 2010 to 5.01% and in that year there were several policies that were less effective so that the purpose of this study is to see how credit is developing nationally and also at the province, then to see what factors will affect credit, then to see how the effectiveness of monetary policy is on total credit, GDP, inflation, using the multiple OLS method and the VAR method to prove the purpose of the research. The results of the research on policy interest rate variables (BIRATE), Gross Domestic Product (GDP) and inflation (INF) have a significant effect on total credit at α 10%, and monetary policy when shocks to policy interest rates, the response from interest rates loans, Gross Domestic Product Inflation is effective when after 2 years the policy is implemented.